Catalytic approaches for the removal of microplastics from water: Recent advances and future opportunities - Miranda Zoppas, Fernanda (2023)
Microplastics, which are small plastic particles, have become a growing environmental concern due to their prevalence in aquatic and terrestrial environments. They persist for decades and potentially centuries due to their resistance to degradation and can harm organisms and release toxic chemicals. There has been increasing interest in developing methods for their removal from the environment, particularly from water. Catalytic processes have shown promise as a potential method for microplastic elimination, including oxidation, hydrolysis, and adsorption. This review article focuses on recent advances in catalytic processes for the removal of microplastics from water, including various types of catalysts and their applications. It also discusses the potential for catalytic processes to be integrated into real-world water treatment systems for the removal of microplastics. The review highlights the challenges and opportunities associated with the removal of microplastics from the environment and aims to contribute to the development of more effective and sustainable methods for addressing this growing environmental issue. Future research should focus on developing hybrid catalyst systems that combine the strengths of multiple processes for improved efficiency and effectiveness. Additionally, research should explore the use of natural materials and biological processes or microplastic elimination, which may offer more sustainable and environmentally friendly options. Collaboration between scientists, engineers, policymakers, and the public will be critical for the development and implementation of these systems. The elimination of microplastics from the environment requires a multifaceted approach, and continued research and collaboration are necessary to develop effective and sustainable methods for their removal and to protect the health of our environment and communities.